Oval slides in triangular spaces? Anchoring national human rights institutions in 'tripartite' Commonwealth Africa - Kotey, Nii Ashie (University of Pretoria, 2006)
Prepared under the supervision of Prof. Nii Ashie Kotey at the Faculty of Law, University of Ghana, Legon